The Effect Of Electronic Service Quality And Perceived Value On Consumer Satisfaction With Trust As A Mediation (Study on Expedition Service Users in Yogyakarta) - Yovita Ornella Puspaningrum; Endang Tjahjaningsih (JURNAL ECONOMINA, 2026)
This study aims to analyze and test the influence of electronic service quality and perceived value on consumer satisfaction, both directly and indirectly through trust as a mediator. The study was conducted on users of expedition services in the Special Region of Yogyakarta, focusing on Generation Y (born 1981–1996) and Generation Z (born 1997–2010) consumer groups. The research approach used was quantitative with descriptive and causal methods. The research sample consisted of 75 respondents selected using purposive sampling techniques with the criteria of having used expedition services at least 3 times in the past year. The data collection technique used a questionnaire with a Likert scale measurement (1–7). The data analysis method used Multiple Linear Regression Test and Sobel Test to test the mediation effect through SPSS. The results showed that electronic service quality and perceived value had a positive and significant effect on trust. Electronic service quality and trust had a positive and significant effect on consumer satisfaction, while perceived value had no effect and was not significant on consumer satisfaction. Trust was able to mediate the influence of electronic service quality and perceived value on consumer satisfaction.